Acute oxalate nephropathy following kidney transplantation: Report of three cases - Diana Taheri; Alaleh Gheissari; Pooria Shaabani; Seyed Reza Tabibian; Mojgan Mortazavi; Shiva Seirafian; Alireza Merrikhi; Mehdi Fesharakizadeh; Shahaboddin Dolatkhah (Journal of Research in Medical Sciences, 2015)
Calcium oxalate (CaOx) crystal deposition is a common finding immediately after kidney transplantation. However, small depositions of CaOx could be benign while extensive depositions lead to poor graft outcome. Here we report three cases with end-stage renal disease (ESRD), bilateral nephrolithiasis, and unknown diagnosis of primary hyperoxaluria (PH) who underwent a renal transplant and experienced an early-onset graft failure. Although an acute rejection was suspected, renal allograft biopsies and subsequent allograft nephrectomies showed extensive CaOx deposition, which raised a suspicion of PH. Even though increased urinary excretion of CaOx was found in all patients, this diagnosis could be confirmed with further tests including genetic study and metabolic assay. In conclusion, massive CaOx deposition in kidney allograft is an important cause of poor allograft survival and needs special management. Furthermore, our cases suggest patients with ESRD and a history of nephrolithiasis should be screened for elevated urinary oxalate excretion and rule out of PH.